A changed life: the life experiences of patients with psoriasis receiving biological treatment. (1st September 2020) - Trettin, B.; Feldman, S.R.; Andersen, F.; Danbjørg, D.B.; Agerskov, H.
Summary: Background: Psoriasis has a large negative impact on quality of life and is associated with both depression and anxiety. The introduction of biologics has improved treatment outcomes, but the ways in which patients perceive these improvements are not well characterized. Objectives: To investigate the everyday life experiences of patients with psoriasis receiving biological treatment in order to gain an understanding of their needs and to improve the quality of care. Methods: A qualitative narrative methodology was utilized. In total 48 h of participant observations during consultations, and 15 semistructured interviews, were conducted with patients receiving biological treatment. Data were analysed according to Ricoeur's theory of interpretation. Results: Receiving biological treatment was experienced as a turning point, with a significant impact on physical, psychological and emotional levels. However, psychological consequences, such as isolation and social withdrawal, seemed to be a part of the patient's identity; the negative perceptions of psoriasis left marks behind that affected the patient's self‐image. Perceived fear of discontinuation of the biological treatment resulted in insecurity, and patients were reluctant to initiate discussion about these concerns with healthcare professionals. Conclusions: Providing assistance when patients enter the transition of receiving biological treatment may be important. Patients' fear of biological treatment being discontinued is an ongoing issue that healthcare professionals could address.